Effect of royal jelly supplementation on aerobic power output and anaerobic power output: Royal jelly and power output - Taşdoğan, Ali Muhittin; Vural, Mehmet; Özdal, Mustafa; Pancar, Zarife (Progress in Nutrition, 2020)
This study with a placebo-controlled experimental design intends to investigate the effect of Royal Jelly (RJ) on the aerobic and anaerobic power output of sedentary men at a dose of 1000 mg/day. For this purpose, a total of 20 adult sedentary men aged 21 to 23 years were included in this study. The subjects visited the laboratory every day for 15 days between 08:00 and 10:00 to get their portion of royal jelly. The subjects were randomly divided into two groups, namely the experimental group (n = 10 individuals, 1000 mg/day Royal Jelly) and the placebo (n = 10 individuals, corn starch mixed with 1000 mg/day water) group and they took royal jelly in glass bottles at the same hour during these visits. In both groups, aerobic and anaerobic power measurements were performed in the laboratory one day before and after the 15-day period. 2×2 mixed factor ANOVA and LSD tests were used to analyze data obtained from the experimental and the placebo group. No significant difference was found in the analysis performed between the pre- and post tests for anaerobic power outputs of the placebo group (p>0.05). Concerning the anaerobic power output of the experimental group, there was a significant difference in the fatigue index value in favor of the post-test (p<0.05). The intergroup analysis of the difference between pre- and post-test in the same parameter showed a significant difference in favor of the experimental group (p<0.05). In the pre-test and post-test analysis of the aerobic power outputs of the placebo group, no significant difference was found (p>0.05). A significant difference was found in the pre- and post-test analysis of the experimental group in favor of the post-test in terms of aerobic power output (p<0.05). The intergroup analysis of the difference between pre- and post-test showed a significant difference in favor of the experimental group in terms of aerobic power outputs (p>0.05). Consequently, it can be argued that royal jelly supplementation taken daily for 15 days at 1000 mg has a positive effect on the aerobic capacity of sedentary men.